Analisa Monday Effect Dan Friday Effect Pada Perusahaan Ekonomi Kreatif Subsektor Fesyen Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Novi Sugiartik; Jeni Susyanti; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the differences in stock returns on Monday to Friday, the Monday effect and the Weekend effect on stock trading on the Indonesia Stock Exchange (IDX) in the period August 2018-July 2019. Creative economy companies fashion subsector listed on the Exchange The Indonesian Effect (IDX) is the population used in this study. The sample selection used a purposive sampling method of 14 selected companies in accordance with predetermined criteria. The type of data used in this study is secondary data. Data analysis methods used in this study are descriptive statistical tests, normality tests and different tests (one sample t-test) for hypothesis testing. The results of this study are (1) there is no difference in stock returns on Monday to Friday on stock trading on the Indonesia Stock Exchange (2) there is no Monday effect phenomenon on stock trading on the Indonesia Stock Exchange and (3) No Weekend effect occurs on trading shares on the Indonesia Stock Exchange.Keywords: Return, Monday effect, Weekend effect